Hepatolenticular degeneration - O. Yu. Koryagina; L. P. Nazarenko; M. N. Philimonova (Бюллетень сибирской медицины, 2005)
Hepatolenticular degeneration or Wilson's disease is the hereditary disease, caused by derangement of copper metabolism and its precipitation in brain and internal. Stages of disease study and development of its nosologic independence are emphasized. Molecular genetic mechanisms of hepatolenticular degeneration, its pathogenesis and clinical classifications are stated. Principal laboratory indices and pathogenetic therapy of Wilson’s disease is represented.